2002
DOI: 10.1523/jneurosci.22-16-06920.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Glial Cell Line-Derived Neurotrophic Factor Mediated by an Adeno-Associated Virus Vector in a Transgenic Animal Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a relentlessly progressive lethal disease that involves selective annihilation of motoneurons. Glial cell line-derived neurotrophic factor (GDNF) is proposed to be a promising therapeutic agent for ALS and other motor neuron diseases. Because adeno-associated virus (AAV) has been developed as an attractive gene delivery system with proven safety, we explored the therapeutic efficacy of intramuscular delivery of the GDNF gene mediated by an AAV vector (AAV-GDNF) in the G93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
132
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(140 citation statements)
references
References 41 publications
3
132
0
2
Order By: Relevance
“…At present, treatment for ALS is mainly palliative [1], although the administration of neurotrophic growth factors as a means to protect motorneurons is being analysed [2]. In vitro studies demonstrated that several neurotrophic factors delay motorneuron degeneration [3][4][5][6]. However, clinical trials using subcutaneous and intrathecal neurotrophic factors caused several side effects such as weight loss, fever, cough, fatigue and behavioural changes [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At present, treatment for ALS is mainly palliative [1], although the administration of neurotrophic growth factors as a means to protect motorneurons is being analysed [2]. In vitro studies demonstrated that several neurotrophic factors delay motorneuron degeneration [3][4][5][6]. However, clinical trials using subcutaneous and intrathecal neurotrophic factors caused several side effects such as weight loss, fever, cough, fatigue and behavioural changes [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…During embryonic development, approximately half of the motoneurons generated undergo programmed cell death (PCD) (Oppenheim, 1991). Motoneuron survival and differentiation depend on trophic factors secreted from target muscle fibers and Schwann cells surrounding motor axons (Bordet et al, 2001;Acsadi et al, 2002;Wang et al, 2002;Lu et al, 2003). Reductions in skeletal muscle activity improve the access of a motoneuron to target-derived trophic factors by increasing the extent to which motor axons branch and form neuromuscular synapses (Oppenheim et al, 2000b;Millecamps et al, 2001Millecamps et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…A number of neurotrophic factors have been proposed as being a promising avenue for gene therapy in light of their beneficial effects on animal models of ALS. Among the factors which have shown promise in facilitating neuroprotection in animal models are vascular endothelial growth factor (VEGF) [81][82][83][84], hepatocyte growth factor (HGF) [85], glial-derived neurotrophic factor (GDNF) [84,86,87], insulin-like growth factor 1 (IGF-1) [88][89][90] and granulocyte-colony stimulating factor (G-CSF) [91,92]. The delivery of these neurotrophic factors can be carried out by using different approaches, with emerging viral vector-based and cell-based therapies among some of the most promising techniques.…”
Section: Dysregulation Of Rna Processing Is Emerging As a Major Pathomentioning
confidence: 99%
“…Engineering AAV viruses to drive neurotrophic factor expression has been successfully tested in ALS mouse models. In the early 2000s it was reported that the intramuscular delivery of GDNF or IGF-1 to SOD1-G93A mice delayed the disease onset, improving behavioural tasks and prolonging lifespan [87,90]. Vascular endothelial growth factor (VEGF) is another promising candidate which has been used as a therapeutic tool in ALS.…”
Section: Dysregulation Of Rna Processing Is Emerging As a Major Pathomentioning
confidence: 99%